Trend Inflation, Taylor Principle and Indeterminacy - Guido Ascari; Tiziano Ropele (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2009)
Even low levels of trend inflation substantially affect the dynamics of a basic new Keynesian DSGE model when monetary policy is conducted by a contemporaneous Taylor rule. Positive trend inflation shrinks the determinacy region. Neither the Taylor principle, which requires the inflation coefficient to be greater than one, nor the generalized Taylor principle, which requires that in the long run the nominal interest rate should be raised by more than the increase in inflation, is a sufficient condition for local determinacy of equilibrium. This finding holds for different types of Taylor rules, inertial policy rules and price indexation schemes. Therefore, re- gardless of the theoretical set up, the monetary literature on Taylor rules cannot disregard average inflation in both theoretical and empirical analysis.
Keywords: E31; E52; 330; Sticky Prices; Taylor Rules and Trend Inflation